As células-tronco como tema gerador para o ensino voltado a divulgação científica e a aprendizagem de Biologia - Cestaro, Débora Cristina (2016)
Technological innovations changed the world, ways of interaction and access to information and knowledge, requiring changes in education also. Brazilian documents such as Parâmetros Curriculares Nacionais (PCN), its complements (PCN+) and Diretrizes Curriculares Nacionais have been proposing a more contextualized teaching and consistent with the new desires of society. A critic citizen formation and “teaching for life” have become recurrent themes in documents, publications about education and schools’ pedagogical staff. However, the objective of many high school students and their families continued to be college acceptance and achievement of a good Exame Nacional de Ensino Médio score. By the current educational context, this study was proposed with the purpose of divulging Brazilian science e producing tools that facilitate the teaching-learning process. Through interaction with the Laboratório de Biologia Básica de Células-tronco (LABCET) of Carlos Chagas Institute/FioCruz, stem cells were utilized as generator theme for the production of an educational object that aims for demystification of the idea that biology prioritize description and memorization, bringing three didactic sequences developed on the subjects of biotechnology and bioethics, embryology and genic expression. Structured according to Pedagogical Moments methodology, these didactic sequences initiate by problematizations, pass through knowledge organization and end at its application. These activities were made available in a portal also developed in this study, entitled “O que a Ciência sabe” (”What Science knows”), that is equipped with complementary materials destined for high school students e Biology teachers.